1998
DOI: 10.1038/sj.gt.3300722
|View full text |Cite
|
Sign up to set email alerts
|

An interaction between penton base and αv integrins plays a minimal role in adenovirus-mediated gene transfer to hepatocytes in vitro and in vivo

Abstract: Studies in cultured cell lines have shown that adenovirus tion of hepatocytes, even though the mutation impaired infection involves binding of adenovirus fiber to its cell surinfection of HeLa cells. Hepatocytes had undetectable face receptor and binding of penton base to ␣v integrins.amounts of ␣v integrins on their cell surface and showed However, much less is known about the role of these interno specific adherence to vitronectin, the natural substrate actions in cells that are targets for adenovirus-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
(38 reference statements)
2
14
0
Order By: Relevance
“…The absence of significant accumulation of radioactivity in the liver suggests that once bound to CAR molecules on the hepatocyte surface, knob is rapidly delivered to an intracellular compartment where it is exposed to deiodinase activity. Consistent with this model of integrin-independent uptake of knob, an earlier study showed that adenovirus-CAR complexes on rat hepatocytes can be internalized by an integrin-independent pathway (18).…”
Section: Discussionsupporting
confidence: 60%
“…The absence of significant accumulation of radioactivity in the liver suggests that once bound to CAR molecules on the hepatocyte surface, knob is rapidly delivered to an intracellular compartment where it is exposed to deiodinase activity. Consistent with this model of integrin-independent uptake of knob, an earlier study showed that adenovirus-CAR complexes on rat hepatocytes can be internalized by an integrin-independent pathway (18).…”
Section: Discussionsupporting
confidence: 60%
“…However, MHC class I level was not observed to be associated with adenovirus transduction efficiency, 34,37 though it was found to be adenovirus type 5 fiber receptor. 15 Furthermore, integrins v 3 and v 5 did not appear to be absolutely necessary for efficient adenovirus transduction of respiratory epithelial cells, 38 39 in contrast to previous reports that integrins v 3 and v 5 were necessary for adenovirus entry. 16,24 Nevertheless, it was suggested that integrins v 3 and v 5 might be facilitative rather than necessary or limiting for efficient adenovirus entry into the host cell.…”
Section: Discussionmentioning
confidence: 74%
“…For example, hepatocytes express the fiber receptor, CAR, but not the penton receptors, a v integrins, yet are infected efficiently by Ad2. 33 Similarly, canine adenovirus type 2 (CAV-2) and Ad40/41 both efficiently bind CAR but enter cells through an RGD-independent pathway. [34][35][36] In our ongoing studies, we are investigating the molecular and cellular requirements for fiber uptake.…”
Section: Discussionmentioning
confidence: 99%